2020
DOI: 10.1007/s00192-020-04408-z
|View full text |Cite
|
Sign up to set email alerts
|

Is antibiotic prophylaxis necessary in mid-urethral sling surgery?

Abstract: Introduction and hypothesis Antibiotic prophylaxis is commonly used when implanting a mid-urethral sling (MUS) for female stress urinary incontinence. Use of antibiotics may lead to adverse events and the development of antibiotic resistance. This study compared a variety of outcomes after MUS surgery with and without antibiotic prophylaxis using data from the national Norwegian Female Incontinence Registry. Methods Preoperative and 6–12 months pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…No RCT has been conducted comparing use of vaginal mesh for prolapse surgery with or without antibiotics, or for sacrocolpopexy. A national Norwegian registry study on midurethral slings concluded that antibiotic prophylaxis reduced postoperative infections and pain, but not tape exposure 43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No RCT has been conducted comparing use of vaginal mesh for prolapse surgery with or without antibiotics, or for sacrocolpopexy. A national Norwegian registry study on midurethral slings concluded that antibiotic prophylaxis reduced postoperative infections and pain, but not tape exposure 43 …”
Section: Resultsmentioning
confidence: 99%
“…A national Norwegian registry study on midurethral slings concluded that antibiotic prophylaxis reduced postoperative infections and pain, but not tape exposure. 43 Showering or bathing with soap or antiseptic solution to reduce the bacteria count on the skin has been studied. A Cochrane review showed no difference between preoperative skin washing with chlorhexidine solution versus usual soap or placebo, but it demonstrated efficacy of showering with some cleansing method versus no showering.…”
Section: Surgical Site Infection Prophylaxismentioning
confidence: 99%
“…A registry-based cohort study 104 of 28,687 women undergoing midurethral sling implantation showed that AP led to a reduction in the occurrence of postoperative infections and extended pain after surgery but did not offer protection against tape exposure. However, the variations in the success rate were minimal and likely not significant from a clinical perspective.…”
Section: Therapeutic Proceduresmentioning
confidence: 99%